Theoretical and methodological foundations of formation and implementation of priorities of regional of cluster policy - Ржепішевська, В. В.; Христенко, О. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The role of the cluster policy in the regional development, its purpose and priorities are discussed in the paper. The key objectives to support cooperative projects under the promotion of cluster associations are defined. The directions providing guidance, information and counseling, educational support cluster policy in the region are offered, as well as actions aimed at preventing risks of ineffective implementation are proposed by authors.